Analisis Pengukuran Overall Equipment Effectiveness (OEE) Mesin Rice Milling Unit di CV Fajar Samudra - Mashabai, Ismi; Ramdani, Marisa Desita; Ulfaturrahmi; Hermanto, Koko (Metode : Jurnal Teknik Industri, 2025)
CV Fajar Samudra is a company that manages rice in Sumbawa. The rice processing process per day can produce + 3 thousand tons of harvested dry grain (GKP) and also produce 50 tons of milled dry grain (GKG) which can later produce around 30 tons of rice. Based on the results of the interview, the problem with the rice grinding machine occurred because the v-belt of the machine broke/loose so that the machine stopped and did not operate for +4 hours. This research uses OEE (Overall Equipment Effectiveness) calculations, namely measuring the level of effectiveness of machine use by calculating machine availability, performance and quality of the products produced. OEE calculates availability, performance and quality. The calculation results from this research show that the availability value is 94.34%, performance 52.44% and quality 99.62%. The OEE value obtained was 47.79% (low). So it can be seen that the highest Losses of CV Fajar Samudra on the rice milling unit machine is the Reduce speed Losses of 39.33% in October 2023.